UNDERWRITER RESPONSIBILITIES IN POLICY CLOSING LIFE INSURANCE - Harahap, Eka Putriani; Sativa, Annisa (Academy of Education Journal, 2023)
Every human being must face a risk. The way to deal with the possibility of an unexpected event is by transferring the risk to another party through an insurance agreement. The research was carried out using a normative juridical approach, especially the statutory approach, where the relevant laws and regulations will be studied in relation to the main issues that the author examines. The author draws the conclusion, based on research, that the Underwriter is responsible for setting selection standards and making decisions for all prospective customers until the policy is issued. An Underwriter is bound to make mistakes in their work. However, the Civil Code has regulated the responsibilities of employers and workers to address this issue. Article 1367 of the Civil Code states that because the insurer works for a company, the insurer will be held liable if a lawsuit occurs involving an error in the underwriting process. Thus, the rights of insurance policy holders remain protected